An Objective Instrument for Assessment of Erikson's Developmental Conflicts. Presentation Summary - Speisman, Joseph C. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
An objective measure of Erikson's ego-identity construct is being developed. The total scale includes seven relatively independent subscales designed to reflect the residuals (part conflicts) of Erikson's psychosocial stages of development. An initial item pool of 194 items has been reduced to 113 items by means of judgemental and statistical analyses. Internal consistency of the total scale is acceptable (Alpha .91, N = 94, and Alpha .836, N =120 at different administrations). Internal consistency for all but two subscales (3 and 6) is also acceptable (Hoyt range is .69 to .84). Test-retest reliability is .72 for the total scale. Significant correlations in predicted directions are achieved with measures of anxiety, self-esteem, ego-control, and social desirability. Construct validation is quite promising thus far, and additional analyses with a large group of young adult subjects are also being performed. (Author)
Sponsoring Agency: National Inst. of Mental Health (DHHS), Rockville, MD.
Contract Number: MH31719.
ERIC Note: Paper presented at the Annual Meeting of the American Psychological Association (91st, Anaheim, CA, August 26-30, 1983).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Anxiety; Correlation; Developmental Stages; Higher Education; Item Analysis; Predictive Measurement; Rating Scales; Self Concept; Self Esteem; Statistical Analysis; Test Construction; Test Reliability; Test Validity; Ego Development Theory; Crowne Marlowe Social Desirability Scale -- Erikson (Erik) -- Rosenberg Self Esteem Scale -- Rotter Internal External Locus of Control Scale -- Social Desirability -- Taylor Manifest Anxiety Scale; Reports, Research; Speeches/Meeting Papers